2019
DOI: 10.1001/jama.2018.18743
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nonmyeloablative Hematopoietic Stem Cell Transplantation vs Continued Disease-Modifying Therapy on Disease Progression in Patients With Relapsing-Remitting Multiple Sclerosis

Abstract: IMPORTANCE Hematopoietic stem cell transplantation (HSCT) represents a potentially useful approach to slow or prevent progressive disability in relapsing-remitting multiple sclerosis (MS). OBJECTIVE To compare the effect of nonmyeloablative HSCT vs disease-modifying therapy (DMT) on disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
273
0
13

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 244 publications
(292 citation statements)
references
References 26 publications
6
273
0
13
Order By: Relevance
“…The main differences between protocols relate to the conditioning agents and their doses, which correspondingly impact both the degree of immunoablation and myeloablation as well as toxicity 1 . While the Canadian protocol involved busulfan, high doses of cyclophosphamide and antithymocyte globulin (ATG) for conditioning, other regimens use a less toxic regimen of lower‐dose cyclophosphamide and ATG, and no busulfan whatsoever 34,35 . Although the toxicity profile of busulfan for IAHSCT in MS 3 has been optimized through improved patient selection, lower dosages, and IV administration, this alkylating agent is known to cause neurotoxicity at higher doses 36 .…”
Section: Discussionmentioning
confidence: 99%
“…The main differences between protocols relate to the conditioning agents and their doses, which correspondingly impact both the degree of immunoablation and myeloablation as well as toxicity 1 . While the Canadian protocol involved busulfan, high doses of cyclophosphamide and antithymocyte globulin (ATG) for conditioning, other regimens use a less toxic regimen of lower‐dose cyclophosphamide and ATG, and no busulfan whatsoever 34,35 . Although the toxicity profile of busulfan for IAHSCT in MS 3 has been optimized through improved patient selection, lower dosages, and IV administration, this alkylating agent is known to cause neurotoxicity at higher doses 36 .…”
Section: Discussionmentioning
confidence: 99%
“…HSCT has been used for hematological malignancies since the 1950s and offers the advantage of being a one‐time procedure. It has previously been reported that treatment with HSCT for RRMS leads to improvement in disability and sustained disease remission for up to 5 years . It is at present unknown if these results can be generalized to 10 years and beyond.…”
Section: Introductionmentioning
confidence: 96%
“…The proportion of patients with no disease activity was 98.1% at 1 year, 90.3% at 3 years, and 78.5% at 5 years in the haematopoietic stem cell transplantation group. These ratios were 20.8%, 5.93%, and 2.97% respectively for the DMT group . Because of severe side effects, haematopoietic stem cells may be an alternative for severe pedMS.…”
Section: Multiphasic Diseasementioning
confidence: 94%
“…These ratios were 20.8%, 5.93%, and 2.97% respectively for the DMT group. 25 Because of severe side effects, haematopoietic stem cells may be an alternative for severe pedMS.…”
Section: Autologous Haematopoietic Stem Cell Transplantationmentioning
confidence: 99%